A Pragmatics Analysis of Positive Comments on TikTok Trend "30 Days English Speaking Challenge" - Annafiyah, Hani; Mujazin, M; Wijayanto, Agus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The study aims to identify the type of speech acts found in positive comments on the TikTok trend "30 Days English speaking Challenge" and to explore the contextual function of these speech acts in the comments section. Methodology: This study used a descriptive qualitative approach. The data in this study were collected using purposive sampling by selecting positive English comments from the video trends in TikTok account @alelcipta uploaded from July to August 2025. The comments were chosen based on relevance to the content of the challenge videos and their suitability for the research focus in terms of speech acts. The data were analyzed using qualitative analysis techniques as proposed by Miles and Huberman (1994) which consist of data reduction, data display, and conclusion drawing/verification. The technique used included documentation by taking screenshots of comments and analyzed according to Searle's (1979) classification of speech acts-assertive, directive, commissive, expressive, and declarative. Then the data analyzed in greater depth to represent the functions or meanings behind the types of speech acts. Results: This study shows there are five types of speech acts identified, except for declarative speech acts. A total of 145 positive comments were found, with the details : assertive (30), directive (37), commissive (7), and expressive (71). Applications/Originality/Value: This study has the potential to highlight the role of positive feedback in building self-confidence and motivation to learn, especially for English learners in online communities, as well as enriching the creation of a supportive and constructive environment on social media.